Discurso chamánico,ordenamiento territorial y áreas protegidas en la Amazonía Colombiana (2005)
RESUMEN:The discourses ofAmazonia’s leaders appropriate the environmental discourse as apolitical strategy to defend the indigenous lands and strengthen the traditional author-ities.Nevertheless,a careful analysis ofthe territorial plans designed by the Indianorganizations from the lower Caquetá river and the surrounding area reveals the forceofthe shamanic discourse,which adjusts the interaction between human beings andother natural species and shows how environmental discourse’s usual concepts areadapted to the native world-view.The Miraña’s decision to manage the CahuinaríNational Park with the ofﬁcials ofthe National Environmental System cannot be under-stood as the expression ofa protectionist position.It should be interpreted,rather,as away to conﬁrm their authority upon a territory that has belonged to them since beforethe creation ofthe park and as a way to control the resources intended for the conser-vation ofthe Amazonian rainforest.